Helicobacter pylori glycan biosynthesis modulates host immune cell recognition and response - Barrett, Katharine A.; Kassama, Francis Jacob; Surks, William; Mulholland, Andrew J.; Moulton, Karen D.; Dube, Danielle H. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The pathogenic bacterium Helicobacter pylori has evolved glycan-mediated mechanisms to evade host immune defenses. This study tests the hypothesis that genetic disruption of H. pylori glycan biosynthesis alters immune recognition and response by human gastric epithelial cells and monocyte-derived dendritic cells. Methods To test this hypothesis, human cell lines were challenged with wildtype H. pylori alongside an array of H. pylori glycosylation mutants. The relative levels of immune response were measured via immature dendritic cell maturation and cytokine secretion. Results Our findings indicate that disruption of lipopolysaccharide biosynthesis diminishes gastric cytokine production, without disrupting dendritic cell recognition and activation. In contrast, variable immune responses were observed in protein glycosylation mutants which prompted us to test the hypothesis that phase variation plays a role in regulating bacterial cell surface glycosylation and subsequent immune recognition. Lewis antigen presentation does not correlate with extent of immune response, while the extent of lipopolysaccharide O-antigen elaboration does. Discussion The outcomes of this study demonstrate that H. pylori glycans modulate the host immune response. This work provides a foundation to pursue immune-based tailoring of bacterial glycans towards modulating immunogenicity of microbial pathogens.